Quality Control Optimization in Carton Production Using Six Sigma SWOT: Optimalisasi Pengendalian Mutu dalam Produksi Karton Menggunakan Analisis SWOT Six Sigma - Adinda Syakina Setiawan; Hana Catur Wahyuni (Indonesian Journal of Innovation Studies, 2026)
This study examines quality control issues in a carton printing company experiencing defect rates exceeding the established standard. General Background: Quality control plays a critical role in maintaining product consistency and competitiveness in manufacturing industries. Specific Background: The observed defect rates in the company surpassed the acceptable threshold, reaching up to 1.6% in recent months. Knowledge Gap: Previous approaches have not fully integrated structured statistical analysis with strategic planning tools to address recurring defects. Aims: This research aims to identify defect types, analyze root causes, and propose improvement strategies using Six Sigma with the DMAIC approach combined with SWOT analysis. Results: The findings indicate an average DPMO value of 3874.569 and a sigma level of 4.16, revealing that the process performance is still below the Six Sigma target. Root causes were identified across five factors: human, machine, method, material, and measurement. Novelty: The integration of Six Sigma and SWOT provides a structured analytical and strategic framework for quality improvement. Implications: The proposed strategies, including SOP standardization, operator training, real-time monitoring, and quality audits, are expected to reduce defects and support sustainable operational performance. Keywords: Quality Control, Six Sigma, SWOT Analysis, Carton Production, Defect Reduction Key Findings Highlights Process capability remains below optimal standards based on sigma level evaluation Root causes consistently originate from five main production factors Strategic integration supports structured quality improvement actions